Competitive lithium and sodium intercalation into sodium manganese phospho-olivine NaMnPO4 covered with carbon black. Issue 106 (15th October 2015) - Boyadzhieva, T.; Koleva, V.; Zhecheva, E.; Nihtianova, D.; Mihaylov, L.; Stoyanova, R.
Abstract : The study demonstrates unusual capabilities of phospho-olivine NaMnPO4 to intercalate lithium and sodium reversibly, which makes it attractive electrode material instead of the conventional lithium analogue LiMnPO4 . Abstract : In this contribution we provide novel data on the reversible lithium and sodium ion intercalation into a sodium-manganese phospho-olivine NaMnPO4, when it is used as a cathode in model lithium-ion cells. The ion-exchange reaction involving the participation of KMnPO4 ·H2 O dittmarite as precursor was chosen for the preparation of NaMnPO4 . The NaMnPO4 particles were covered with carbonaceous materials to improve the electrical conductivity and electrolyte wetting. The procedure includes ball-milling of NaMnPO4 with conductive carbon black additives Super C/65, followed by thermal treatment. The mechanically treated samples consist of well crystallized phospho-olivine phase NaMnPO4 free of any anti-site defects and disordered carbon species with graphite like medium-range order. The composite NaMnPO4 /C material manifests a reversible capacity between 80–85 mA h g −1 in model lithium cells versus lithium anode. Prior to the electrochemical test, the chemical inertness of NaMnPO4 in the lithium electrolyte is studied by soaking phospho-olivines in the solution of LiPF6 in EC:DMC. The mechanism of the reversible intercalation/deintercalation cycling is investigated using ex situ X-ray powder diffraction, TEM and high-angle annular dark field STEM analysis, infrared spectroscopy and electron paramagnetic resonance spectroscopy (EPR). The study demonstrates, for the first time, that NaMnPO4 is able to intercalate reversibly both Na + and Li + ions following the chemical reaction Li x Na1− x MnPO4 ↔ Li0.0 Na0.5 MnPO4 (0.25 ≤ x ≤ 0.45).